Implementasi Pembelajaran Berbasis Masalah (Problem Based Learning) Dalam Pendidikan Agama Islam Di Sekolah Dasar - ariba, sania rosya; Ratih, Silfa (IQRA : JURNAL PENDIDIKAN ISLAM, 2025)
The learning model in elementary schools is still heavily influenced by views that see information as facts that need to be memorized. In many classrooms, the learning process still focuses on the teacher as the main source of information, with lectures as the dominant method. In this situation, students are not given the opportunity to formulate questions or be actively involved in learning. To create an environment that supports the development of creativity and innovation, it is essential to create a balanced relationship between teachers, students, teaching materials, aids, and the assessment techniques and instruments used. With this approach, learning will be more effective. The Problem-Based Learning (PBL) model is considered the right solution. The question then is, how to implement this model in Islamic Religious Education (PAI) learning at the elementary school level?